Посягання на здоров’я людей під приводом проповідування релігійних віровчень чи виконання релігійних обрядів - Кульчинська, Ю.; Kulchynska, Iu. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано підстави кримінально-правової охорони правовідносин, змістом яких є право на свободу віросповідання людини. Обґрунтовано тезу про необхідність запровадити підвищену кримінальну відповідальність за незаконну діяльність згаданих груп. ст.181 КК України має певні вади. У ній передбачається відповідальність тільки для організаторів та керівників деструктивних груп, але нічого не сказано про активних учасників, які всебічно сприяли її функціонуванню. Обґрунтовується необхідність нової редакції ст. 181 КК України, яка дозволить захищати осіб від будь-яких протиправних дій з боку організаторів, керівників та активних учасників деструктивних релігійних чи громадських об’єднань. Також пропонується створити на державному рівні Центр допомоги жертвам деструктивних релігійних та громадських об’єднань. The article analyzes bases for legal relations protection the content of which is the right for freedom of belief. One of the global problems in the sphere of religious relations is the activities of various totalitarian groups within which crimes are committed. The author heightens the need to introduce increased criminal liability for illegal activities of the aforementioned groups. Article 181 of the CC of Ukraine has some shortcomings. It implies criminal liability only for the organizers and leaders of destructive groups, but not for those active members of them, who being aware of the illegality of their activities, comprehensively promoted its activities. A new wording of Article 181 of the CC of Ukraine is suggested which would introduce criminal liability for assault on rights of the individual under pretext of religious or social activities. It will allow to protect both juveniles and adults against illegal actions of the leaders or active members of the religious or public destructive groups and associations. The author, taking into account international experience, also proposes to establish at the national level Center of assistance to the victims of the religious or public destructive groups and associations.
Assault on health of people caused by preaching religious beliefs and performance of religious rites
Keywords: гарантії свободи віросповідання; тоталітарні групи; нетрадиційні культи; guarantees for freedom of belief; totalitarian groups; non-traditional cults